Investigation of the Quality and Mechanical Properties for SpotWelding of Reworked Galvannea and High Strength Steel (HSS) / Mohd Harris Fadhilah Zainudin ... [et al.] - Zainudin, Mohd Harris Fadhilah; Khashi'ie, Najiyah Safwa; Ab Rahim, Muhammad Saiful Ridzwan (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
Resistance spot welding is one of the factors that determine the crashworthiness of a vehicle. It is quite normal that in the automotive industry the outer panel is being stoned using whetstone when the worker is trying to find the defect at the panel. The aim of this study is to investigate the welding quality and mechanical properties of 2 layer welding sheet containing a reworked galvanneal metal sheet with HSS. Another set of material consisted of non-reworked galvanneal metal and HSS were welded together as the reference. The welded samples were prepared according to the ISO 14273:2000. Welding parameters for both types of samples were kept the same. The tensile strength, hardness and microstructure of the welded material were checked and the nugget diameters were compared tone another. Based on the results, it was concluded that the rework process of the galvanneal metal sheet did not change much the quality and the mechanical properties of the spot welding.